Adding methylphenidate to prism-adaptation improves outcome in neglect patients. A randomized clinical trial. (September 2018) - Luauté, Jacques; Villeneuve, Laurent; Roux, Adeline; Nash, Stuart; Bar, Jean-Yves; Chabanat, Eric; Cotton, François; Ciancia, Sophie; Sancho, Pierre-Olivier; Hovantruc, Patrick; Quelard, François; Sarraf, Thierry; et al.
Abstract: Spatial neglect is one of the main predictors of poor functional recovery after stroke. Many therapeutic interventions have been developed to alleviate this condition, but to date the evidence of their effectiveness is still scarce. Objective: The purpose of this study was to test whether combining prism adaptation (PA) and methylphenidate (MP) could enhance the recovery of neglect patients at a functional level. Methods: RITAPRISM is a multicentre, randomized, double-blind, placebo-controlled study comparing PA plus placebo (control) versus PA plus MP. 24 patients were prospectively enrolled (10 in the placebo group and 14 in the MP group). Results: The main result is a long-term functional improvement (on the functional independence measure (FIM) and on Bergego's scale) induced by MP combined with PA. No serious adverse event occurred. Conclusions: The long-term benefit on activities of daily living (ADL) obtained in this randomized controlled trial set this intervention apart from previous attempts and supports with a high level of evidence the value of combining PA and MP in order to improve the autonomy of neglect patients. Further studies will be needed to clarify the mechanism of this improvement. Although not specifically assessed at this stage, a part of the improvement in ADL might be related to the collateral effect of MP on mood, executive functions or fatigue, and/or the combined effect of PA and MP on motor intentional bias of neglect patients. Classification of evidence: This study provides Class I evidence that adding MP to PA improves the functional outcome of neglect patients. WHO trial registration ID: EUCTR2008-000325-20-FR.